Let's get dirty! Le azioni di depaving dei suoli urbani per la multifunzionalità degli spazi sottoutilizzati (Altre Modernità, 2019)
The presence of underused spaces within urban areas, associated with the need to promote the transformation of such situations to respond to the different needs of communities, has led to the emergence of numerous experiences of depaving. These initiatives, promoted by institutions and groups of citizens, have acted with the aim of: countering the physical degradation of areas located in residential contexts; responding to the needs of communities for a new endowment of collective spaces and protection of places; promoting the principles of sustainability through the creation and management of renaturalized spaces; restoring the permeability of soils to contain the phenomena of flooding of urban areas by applying the principles of sustainable urban drainage.The contribution, after a brief approach to some key issues, will deal with international cases recognizing some conditions that have characterized these experiences. In particular, it is interesting to highlight their ability to translate de-sealing into concrete action, compared to some results consciously sought by the promoters.